Focus on cannabinoids and synthetic cannabinoids. Issue 2 (20th December 2016) - Le Boisselier, R; Alexandre, J; Lelong‐Boulouard, V; Debruyne, D
Abstract : The recent emergence of a multitude of synthetic cannabinoids (SCs) has generated a wealth of new information, suggesting the usefulness of state‐of‐the‐art on lato sensu cannabinoids. By modulating a plurality of neurotransmission pathways, the endocannabinoid system is involved in many physiological processes that are increasingly explored. SCs desired and adverse effects are considered to be more intense than those observed with cannabis smoking, which is partly explained by the full agonist activity and higher affinity for cannabinoid receptors. Neurological and cardiovascular side effects observed after cannabinoid poisoning generally respond to conventional supportive care, but severe outcomes may occur in a minority of cases, mainly observed with SCs. The likelihood of severe abuse and addiction produced by SCs are of concern for the scientific community also interested in the potential therapeutic value of cannabinoids.